Edukasi Pencatatan Kas Sederhana sebagai Upaya Mengurangi Risiko Keuangan pada UMKM (Studi pada UMKM Risolesnya Bunda, Kantin Universitas Riau) - Dea Elsani; Roza Fitrialis; Nashwa Putri Nabila; Annie Mustika Putri (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an importantrole in driving the local economy, including within universityenvironments, as represented by the MSME “Risolesnya Bunda”operating in the canteen of Universitas Riau. In practice, thisbusiness partner still manages its finances irregularly: income andexpenses are not consistently recorded, and business funds are oftenmixed with personal funds, making it difficult for the owner todetermine the actual financial condition and increasing the risk offinancial mismanagement. This community service program aims toprovide education on the importance of simple cash recording as aneffort to reduce financial risk in MSMEs. The implementation methodconsisted of preparation, socialization, training in preparing asimple cash book, hands-on practice in recording transactions, anddiscussion sessions. The results show an improvement in thepartner’s understanding of how to separate personal and businessfunds, how to record income and expenses, and an introduction to adigital recording alternative using a Google Form linked to aspreadsheet. Through this activity, the partner obtained a simplecash book that can be used independently and sustainably to supportmore orderly financial management